Cervical infection with human papillomavirus (HPV) 6 or 11 in high-risk women in Burkina Faso. Issue 5 (21st April 2010) - Low, Andrea; Didelot-Rousseau, Marie-Noelle; Nagot, Nicolas; Ouedraougo, Abdoulaye; Clayton, Tim; Konate, Issouf; Van de Perre, Philippe; Segondy, Michel; Mayaud, Philippe
Abstract : Background: Human papillomavirus (HPV) types 6 and 11 are known agents of genital warts but little is known about their epidemiology in Africa. Objective: To present data on the prevalence of, and risk factors for, cervical HPV 6 and 11 in high-risk women in Burkina Faso. Methods: 306 women were enrolled. HIV status and CD4+ counts were determined. Among other genital samples, a cervical swab (Cervex) was collected for liquid-based cytology and HPV genotyping using MY09/MY11 and GP5+/GP6+ PCRs, and INNO-LiPA genotyping v2. Risk factors were examined using logistic regression. Results: HIV-1 seroprevalence was 40% (123/306). Cervical HPV DNA was detected in 55% (100/183) of HIV-uninfected women, 84% (78/93) of HIV-1 infected women with CD4+ T-cell counts >200 cells/μl and 97% (29/30) of HIV-1 infected women with CD4+ T-cell counts ≤200 cells/μl (ptrend <0.001). HPV 6 prevalence was 6% (18/306), HPV 11 prevalence 4% (13/306), and overall HPV 6/11 prevalence 9% (28/306), which increased with HIV infection and immunosuppression. Genital warts were associated with HPV 6 (adjusted OR=4.12, 95% CI 1.17 to 14.53) but not with HPV 11. Genital ulcerations were associated with HPV 6/11 but not with other HPV types. There was a protective effect for vaginal douching and the follicular phase of the menstrual cycle. Condom use, HIV-1 plasma viral load and sexually transmitted and other reproductive tract infections were not associated with HPV 6/11. Conclusions: Prevalence of HPV 6/11 was high in this population, with predominance of HPV 6. HPV 6/11 were found more frequently in women with genital ulcers and in those with HIV-related immunosuppression.